Russia, the conflict in Ukraine and the new spatial and geopolitical order - Thomann, Pierre-Emmanuel (Sociološki pregled, 2023)
The conflict in Ukraine is the subject of contradictory narratives in the communication war, but also reflects the rival historical and geopolitical representations between the different actors of this conflict. According to the geopolitical angle, the main issue of the crisis in Ukraine is the rivalry between the great powers for world power and the distribution of geopolitical spaces. The geopolitical angle thus makes it possible to take into account the numerous stakes linked to this crisis on different scales, which go well beyond the purely geostrategic and military aspects. The main hypothesis of this article is to determine to what extent Russia, with its special military operation in Ukraine, is pushing for the emergence of a new geopolitical configuration on a European and global scale. Indeed, Moscow is provoking a redefinition of alliances at the regional and global levels. At the Eurasian level, NATO will probably no longer be able to pursue a policy of expansion in the Russian near abroad (countries of the former USSR), the enlargement of NATO to Ukraine being a casus belli, as the Russian intervention has shown. On a global scale, Russia’s membership in the UN Security Council now prevents any unilateral interpretation of international law by the collective West. Moreover, economic sanctions by EU and NATO member states are not being followed by other states in Eurasia, South America and Africa, challenging the unipolar project of the West under the leadership of the United States. The European Union is increasingly aligned with the geopolitical priorities of NATO and the United States, with little room for manoeuvre. Russia’s special operation in Ukraine is definitely moving the world towards a multicentric and multipolar geopolitical configuration, with no possibility of returning to the pre-conflict situation. In this analysis, geopolitical cartography will be used to illustrate the problematics but also to emphasize the spatial angle as an analytical tool.
Keywords: Russia; Ukraina; geopolitical order; patial order